Arabic Hack: Arabic Language Learning Methods in the Digital Era - Hadid Asfar; Ilya Husna; Saidur Rahman (Arabiyyatī: Journal of Arabic Language Education, 2024)
The digital era has brought significant changes in Arabic language learning methods, presenting new opportunities and challenges for learners and teachers. This research examines various Arabic learning methods that can be implemented in the digital era such as mobile applications, e-learning platforms, and social media. This research is a literature study with a qualitative descriptive approach. The data is taken from the latest sources in the form of books, journals, articles, web, and so on. The data collection technique was carried out with documentation techniques. Data analysis used content analysis. The findings of this study include Arabic language learning media Online Class (E-Learning) such as Moodle, Zoom Meeting, Google Classroom and Offline Classroom learning media (Conventional) such as LCD Projector, Video and Audio, Computer, Tablet, Smartphone. Thus the conclusion is that the use of digital technology in Arabic language learning is very effective in increasing student interaction, engagement, and learning motivation. Digital technology can also adapt to individual learning needs and styles. However, challenges such as limited technological infrastructure, digital skills of teachers and students, and gaps in internet access still need to be overcome. A balanced integration between online and offline learning methods can provide optimal results in Arabic language acquisition in the digital era.